PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Maria Brigita Niis Nana; Justin Eduardo Simarmata; Lailin Hijriani (Program Studi Pendidikan Matematika, 2024)
This research aims to determine the influence of a realistic mathematics learning approach on the creative thinking abilities of class VII students on the subject of Himpunan at SMP Negeri 1 Malaka Timur. The population size in this study is 81 students and the sample size of 18 students. The type of research used in this research is quasi-experimental research. The design used in this research is The One Group Pretest-Posttest Design, while the data collection technique uses the test method. The data analysis technique uses t-test statistics. The results show that students' creative thinking abilities using Realistic Mathematics Education (RME) obtained a significant value < 0.05, namely 0.001 < 0.05, so H1 is accepted and this means that the Realistic Mathematics Education learning approach influences students' creative thinking abilities.